Craftsman of the Cumberlands : Tradition and Creativity. - Jones, Michael Owen (Publications of the American Folklore Society. New series (Unnumbered), 1989)
Why do people consider aesthetic qualities as well as utilitarian ones in the making of everyday objects? Why do they maintain traditions? What is the nature of their creative process? These are some of the larger questions addressed by Michael Owen Jones in his book on craftsmen in the Cumberland Mountains of eastern Kentucky. Concentrating on the work of one man, woodworker and chairmaker Chester Cornett, Jones not only describes the tools and techniques employed by Cornett but also his aspirations and values. Cornett possessed a deep knowledge of his materials and a mastery of construction.